Clinical features and outcomes after endovascular therapy for penetrating aortic ulcer and intramural hematoma. (April 2022) - Jiang, Xiaolang; Liu, Yifan; Chen, Bin; Jiang, Junhao; Shi, Yun; Ma, Tao; Lin, Changpo; Guo, Daqiao; Xu, Xin; Fu, Weiguo; Dong, Zhihui
Objectives: To identify the differences between clinical features and outcomes after endovascular therapy for penetrating aortic ulcer (PAU) and intramural hematoma (IMH). Methods: From January 2009 to March 2020, patients who underwent endovascular therapy for PAU and IMH were enrolled. Information on patient demographics, presentation, PAU and IMH morphology, laboratory examination, and clinical follow-up information was collected and analyzed. Univariate analysis was performed to identify the differences between IMH and PAU, and Kaplan–Meier was used to calculate the cumulative survival rate and freedom from reintervention. Results: A total of 114 patients were enrolled; 80 (70.2%) of them were diagnosed with PAU. Compared with PAU, patients with IMH were younger ( p = 0.006), more likely to be admitted emergently ( p = 0.001), had longer hospital stay ( p = 0.028), and had higher levels of C-reactive protein ( p = 0.030). Meanwhile, patients with IMH were more likely to be associated with hypertension ( p = 0.020) and pleural effusion ( p < 0.001) and less likely to have a history of acute coronary syndrome ( p = 0.019) and prior cardiovascular intervention ( p = 0.017). The five-year freedom from reintervention and cumulative survival rate were 94.2% (95% confidential interval, 88.9%–99.9%) and 87.8% (95% confidential interval, 79.5%–96.9%) in PAU patients and 89.6% (95% confidential interval, 75.8%–99.9%) and 85.1% (95% confidential interval, 68.0%–99.9%) in IMH patients, respectively. There was no significant difference in freedom from reintervention ( p = 0.795) or cumulative survival rate ( p = 0.817). Conclusions: IMH appeared to occur in younger patients with hypertension and usually had an acute onset, while PAU was more likely to be found incidentally in older patients with atherosclerosis. Endovascular therapy was effective in both IMH and PAU patients with encouraging outcomes.